THE ROLE OF THE FLAVODIIRON PROTEINS IN NITRIC OXIDE DETOXIFICATION - Vicente, João Filipe Bogalho (2019)
"This dissertation portrays recent developments on the knowledge of a protein family whose once elusive role is presently clearer, although still prone to discussion. The family of Flavodiiron Proteins (FDPs), initially thought to protect anaerobes from oxygen exposure, have been proposed to have a role in nitric oxide detoxification. The main object of study of this dissertation, Escherichia coli Flavorubredoxin (FlRd) made a large contribution to establish this role. FlRd was the first member of the FDP family to be assigned as an NO reductase, followed by the demonstration of the same activity in other FDPs, although a role in oxygen scavenging by other FDP family members has to be considered.(...)"